Maternal Adverse Childhood Experiences, Family Strengths, and Chronic Stress in Children. Issue 3 (May 2019) - Condon, Eileen M.; Holland, Margaret L.; Slade, Arietta; Redeker, Nancy S.; Mayes, Linda C.; Sadler, Lois S.
Abstract : Background: Researchers have demonstrated that maternal adverse childhood experiences (ACEs), such as abuse and neglect, are associated with prenatal risk factors and poor infant development. However, associations with child physiologic and health outcomes, including biomarkers of chronic or "toxic" stress, have not yet been explored. Objectives: The purpose of this study was to examine the associations among past maternal experiences, current maternal posttraumatic stress disorder (PTSD) symptoms, and children's indicators of exposure to chronic stress in a multiethnic sample of mothers and children at early school age (4 to 9 years). Methods: This cross-sectional study included maternal–child dyads ( N = 54) recruited from urban community health centers in New Haven, Connecticut. Mothers reported history of ACEs, family strengths, and current PTSD symptoms. Child measures included biomarkers and health and developmental outcomes associated with chronic stress. Correlational and regression analyses were conducted. Results: Childhood trauma in mothers was associated with higher systolic blood pressure percentile ( ρ = .29, p = .03) and behavioral problems ( ρ = .47, p = .001) in children, while maternal history of family strengths was associated with lower salivary interleukin (IL)-1β ( ρ = −.27, p = .055), salivary IL-6 ( ρ = −.27, p = .054), and body mass index z -scores ( ρ = −.29, p = .03) in children. Maternal PTSD symptoms were associated with more child behavioral problems ( ρ = .57, p < .001) and higher odds of asthma history ( ρ = .30, p = .03). Discussion: Results indicate that past maternal experiences may have important influences on a child's health and affect his or her risk for experiencing toxic stress.